High rate of hepatitis B virus mother-to-child transmission in Lao People’s Democratic Republic - Prapan Jutavijittum (2018)
© 2016, SEAMEO TROPMED Network. All rights reserved. Hepatitis B virus infection is endemic in Lao People’s Democratic Republic (PDR). Among 3,000 pregnant women attending an antenatal clinic at Mother and Child Hospital in Vientiane, Lao PDR, 5.8% were HBsAg positive by a rapid test. Among serum samples of 47 infants aged 9-12 months born to HBsAg-positive mothers, 38% were anti-HBs negative. Percent anti-HBs negative children is significantly higher in those born to HBeAg positive mothers than in those born to HBeAg negative mothers (60% vs 25%, p < 0.05). Out of 47 HBsAg-positive mothers, 10 had infants who were HBsAg positive. None of the infants born to HBeAg negative mothers became HBsAg positive but 10/19 (52.6%) of infants born to HBeAg positive mothers became HBsAg positive. This high rate of mother-tochild transmission of HBV in an endemic country is of concern and indicates that routine vaccination program for Lao infants needs strengthening.